2018
DOI: 10.1002/jctb.5643
|View full text |Cite
|
Sign up to set email alerts
|

Media photo‐degradation in pharmaceutical biotechnology – impact of ambient light on media quality, cell physiology, and IgG production in CHO cultures

Abstract: BACKGROUNDMany vital components in bioprocess media are prone to photo‐conversion or photo‐degradation upon exposure to ambient light, with severe negative consequences for biomass yield and overall productivity. However, there is only limited awareness of light irradiation as a potential risk factor when working in transparent glass bioreactors, storage vessels or disposable bag systems. The chemical complexity of most media renders a root‐cause analysis difficult. This study investigated in a novel, holistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…The peaks at 523 and 724 cm −1 are associated with the LO and transverse optical (TO) modes of Ta 2 O 5 , respectively. In fact, the peak centered at 1038 cm −1 is found, which is the υ1 symmetric stretching vibrations of the PO 4 3− . As depicted in Fig.…”
Section: Resultsmentioning
confidence: 80%
“…The peaks at 523 and 724 cm −1 are associated with the LO and transverse optical (TO) modes of Ta 2 O 5 , respectively. In fact, the peak centered at 1038 cm −1 is found, which is the υ1 symmetric stretching vibrations of the PO 4 3− . As depicted in Fig.…”
Section: Resultsmentioning
confidence: 80%
“…The 2D EEM matrix of the second supplier media batches had a decreased peak at ex450 nm/em530 nm when compared to the reference media (data not shown). This peak is known to be strongly influenced by riboflavin [5]. Finally, the riboflavin content of the reference media basal powder and the second supplier basal powder were analyzed and the results confirmed that the riboflavin content in the reference media was indeed significantly elevated in comparison to the second supplier basal powder.…”
Section: Fingerprint At the End Of The Media Batchesmentioning
confidence: 66%
“…Besides analytical and biological variability, a major source for variable process performances is often reported to be linked to the chemical media composition . Cell culture media often consist of more than 50 components, including substances with known stability issues such as cysteine, insulin, and riboflavin . Quality control for cell culture media may include raw material screening with spectroscopic methods as near‐infrared and mid‐infrared (MIR) spectroscopy .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations